Inhibiting Factors and the Role of Islamic Education Teachers in Develop A morality Student Behavior at MTs Sunan Kalijaga Bojong - Ramadan Rowing (Yayasan Baru Haji Samsudin, 2025)
The research was conducted to examine the inhibiting factors and the role of teachers in developing students' moral behavior at MTs Sunan Kalijaga Bojong. This study employed a qualitative research design with a case study approach, utilizing interviews and documentation techniques with Islamic Education (PAI) teachers as the primary research subjects. The findings reveal several factors that hinder the development of students’ moral behavior. These factors include family background, social environmental influences, and the pervasive impact of social media, all of which contribute to the challenges faced by PAI teachers in promoting ethical conduct among students. In response to these challenges, teachers implement various strategies to foster moral development. These strategies include providing guidance and counseling regarding noble character, delivering warnings and sanctions for inappropriate behavior, consistently mentoring students, and modeling ethical behavior through daily interactions. Furthermore, the research highlights the importance of collaboration between teachers and parents to monitor and reinforce students’ moral development beyond the school environment. By adopting a holistic approach that integrates classroom instruction, parental involvement, and practical guidance, teachers can effectively cultivate students who demonstrate ethical awareness, responsibility, and social consciousness. This study underscores the critical role of teachers in shaping morally upright individuals and offers insights for enhancing character education programs in Indonesian junior high schools